Prenatal diagnosis of hypertrophic cardiomyopathy and myocardial hypertrophy – literature review - Biały, Łucja H.; Respondek-Liberska, Maria (Prenatal Cardiology, 2024)
Hypertrophic cardiomyopathy (HCM) is a rare condition that involves abnormal structure of the sarcomere and can be seen on fetal echocardiography as an excessive growth of the ventricles; it is usually differentiated with myocardial hypertrophy due to maternal diabetes. Both can be diagnosed during fetal echocardiography examination; however, myocardial hypertrophy is a much more common occurrence. Their diagnosis can involve thickening of the walls, and left ventricular outflow tract (LVOT) or right ventricular outflow tract (RVOT) obstruction in rare cases can occur resulting in fetal hydrops and heart failure.